Genetic diversity and relationship between domesticated rye and its wild relatives as revealed through genotyping‐by‐sequencing. (26th March 2018) - Schreiber, Mona; Himmelbach, Axel; Börner, Andreas; Mascher, Martin
Abstract: Rye ( Secale cereale L.) is a cereal grass that is an important food crop in Central and Eastern Europe. In contrast to its close relatives wheat and barley, it was not a founder crop of Neolithic agriculture, but is considered a secondary domesticate that may have become a crop plant only after a transitory phase as a weed. As a minor crop of only local importance, genomic resources in rye are underdeveloped, and few population genetic studies using genomewide markers have been published to date. We collected genotyping‐by‐sequencing data for 603 individuals from 101 genebank accessions of domesticated rye and its wild progenitor S. cereale subsp. vavilovii and related species in the genus Secale . Variant detection in the context of a recently published draft sequence assembly of cultivated rye yielded 55, 744 single nucleotide polymorphisms with present genotype calls in 90% of samples. Analysis of population structure recapitulated the taxonomy of the genus Secale . We found only weak genetic differentiation between wild and domesticated rye with likely gene flow between the two groups. Moreover, incomplete lineage sorting was frequent between Secale species because of either ongoing gene flow or recent speciation. Our study highlights the necessity of gauging the representativeness of ex situ germplasm collections for domestication studies and motivates a more in‐depth analysis of the interplay between sequence divergence and reproductive isolation in the genus Secale .